Exploring Variabels of Teachers Financial Well-Being in Indonesia Jesuit Schools - Andreass Aryono Mantiri; Christiana Fara Dharmastuti (FKIP Universitas Lampung, 2024)
Exploring Variabels of Teachers Financial Well-Being in Indonesia Jesuit Schools. Objectives: This study explored the interrelationships between financial literacy, financial efficacy, financial attitude, financial behavior, and spiritual intelligence in influencing the financial well-being of Indonesian Jesuit school teachers. Methods: A quantitative research approach was employed, utilizing structural equation modeling (SEM-PLS) to analyze data collected from 225 Jesuit school teachers. Data were gathered through a survey instrument designed to measure the variables of interest. Findings: The study found that financial behavior plays a crucial mediating role in the relationship between these variables and financial well-being. Financial efficacy directly predicts financial well-being, while spiritual intelligence and financial attitude indirectly enhance well-being through their influence on financial behavior. Financial literacy, contrary to expectations, does not directly impact financial well-being but indirectly contributes through its influence on financial behavior. Conclusion: The study highlights the importance of fostering positive financial behaviors and integrating spiritual intelligence into financial decision-making to improve the financial health of educators. These findings offer valuable insights for educational institutions and policymakers seeking to enhance the financial well-being of teachers. Keywords: financial well-being, spiritual intelligence, teachers.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202497